INTERPERSONAL RELATIONSHIPS OF YOUNGER STUDENTS INVOLVED IN DANCE SPORTS - Yu. M. Bosenko (Science and Innovation Center Publishing House, 2020)
The article describes the results of diagnostics of the features of interpersonal relations and the study of self-image of younger students (n=77) who are engaged in (n=40) and not engaged in (n=37) dance sports.